Hepcidin Levels in Multi Transfused β Thalassemia Major Patients - MuhammadJawad, Iram Aftab , Muhammad Tahir Saeed, Ghazala Mumtaz , Saima Iram , Shahida Mohsin (Journal of Rawalpindi Medical College, 2016)
Background: To determine and compare the serum hepcidin levels and conventional markers of iron status in patients of β- thalassaemia major with controls. Methods: Forty patients of β- thalassaemia major who were not on iron chelation therapy and 40 normal controls were included in this study. Hemoglobin level, red blood cell count and hematocrit of the study group were determined. Hepcidin levels along with serum iron, serum ferritin and total iron binding capacity were determined . Results:Serum hepcidin level was found to be reduced in patients (426.21 pg/ml) as compared to controls (757.45 pg/ ml). Conclusion: Determination of hepcidin concentration is a useful indicator for high risk of iron toxicity in patients of beta thalassaemia with multiple transfusions